Le castrum de l’Antiquité tardive et du haut Moyen Âge de Mandeure et l’établissement fortifié de hauteur de Château-Julien (Doubs) - David Billoin; Cédric Cramatte (Gallia)
Recent discoveries have deeply renewed the knowledge on the antique town of Mandeure, considered as the major town of the Sequani after the civitas capital Besançon/Vesontio. They allowed to reconsider the town evolution between the Late Iron Age and the Early Middle Ages but above all to understand the extent of changes that the town goes through during the Late Antiquity; the construction of a castrum and of an Early Christian basilica on the spot of a military camp built in the mid-4th c. AD. These results question a well-established historiographical tradition which considered a progressive abandonment of the town during the 4th c. and reports the charts of the 8th c., in which is mentioned the fortified settlement of Mandorum. At the same time, not far below, a hilltop fortified settlement at Château-Julien is established on a strategic control point at the crossing of land and river roads. The presence of these two concomitant power centres raises the question of a territorial restructuring centred on this part of the river Doubs valley.